Assessment of pulmonary function in patients with type 2 diabetes mellitus: a case-control study - Kapoor, Dhiraj; Kumar, Pankaj; Ranjan, Asha; Sharma, Kailash Nath; Dogra, Varun Deep; Bansal, Rekha; Sharma, K. K.; Kumar, Dinesh (International Journal of Research in Medical Sciences, 2017)
Background:As other microvascular complications, respiratory involvement is far less studied among patients with type-2 Diabetes Mellitus (DM). Objective: to study the extent of pulmonary function limitation among patients with type-2 DM. Methods:Hospital based matched case-control study. Results:Total of 90 cases and 90 controls matched for age, sex, height and weight were recruited. Patients with DM had neuropathy [63.3% (57; male=27: Female: 30)], retinopathy [44.4% (40; male=22: Female: 18)], nephropathy [41.1% (37; male=17: Female: 20)] and microalbuminuria [14.4% (13; male=5: Female: 8)]. All cases and 88 controls observed with FEV1:FVC ratio of >70.0%, further assessment for delineation of normal and restrictive pattern patients with high level of predicted values of FEV1 as compare to FVC showed that significantly (P = 0.00) more (Cases: 76.6%; Controls: 42.2%) cases had FEV1 >FVC predicted levels as compare to controls, means among diabetics odds of restrictive pattern of lung abnormality is four times (OR: 4.4; CI: 2.3-8.5) more as compare to non-diabetics. In addition a long duration of DM was significantly (r: 0.39; P = 0.00) positively correlated with lung dysfunction. Conclusion: Patients with type 2 DM patients as compare to its controls observed with restrictive pattern of lung dysfunction.